Synthesis CuInSe2 (CISe) Thin Films Prepared from Metal-Ethanolamine Complex Compound - Ersan Y Muslih; Agus Ismail; Kyoo Ho Kim (Indonesian Journal of Science and Technology, 2017)
CuInSe2 (CISe) thin film was successfully fabricated from copper and indium salts with ethanolamine as precursors. All of these precursors were dissolved and formed complex compounds with ethanolamine simultaneously which deposited on soda lime glass by spin coating at 200 rpm, followed by heat treatment in the ambient atmosphere at 200oC for 120 minutes and finally selenization at 550oC using selenium pellets under Ar (95%) + H2 (5%) for 120 minutes to fabricate CISe thin film. Reaction mechanism, structure, morphology and chemical composition also reported in this work.